Correlates of Genetic and Phenotypic attributes of Taro [Colocasia esculenta (L.) Schott] - Devi, H. Supriya; Singh, Vikas (Indian Journal of Hill Farming, 2019)
An experiment was conducted with 40 Taro germplasm lines to study the genotypic variance, phenotypic variance, phenotypic coefficient of variation (PCV), genotypic coefficient of variation (GCV), heritability (broad sense), genetic advance as percent of mean, correlation coefficient and path coefficient of different characters on tuber yield. The data collected over the genotypes and replications were analysed statistically for correlation studies revealed that tuber yield per plant had positive and significant correlation with number of leaves per plant, pseudostem girth, weight of corm per plant, pseudostem height, average weight of corm, number of corms per plant, number of suckers per plant, weight of cormel per plant, number of cormels per plant and number of days to maturity both at genotypic and phenotypic level suggested that selection based on these traits would ultimately improve the tuber yield per plant. Path coefficient analysis revealed that weight of corm per plant had maximum positive direct effect on tuber yield per plant followed by weight of cormel per plant at genotypic and phenotypic level. Therefore emphasis should be given on weight of corm per plant, weight of cormel per plant and number of leaves per plant, while selecting a good genotype for enhancing the yield of Taro.